2017
DOI: 10.1166/jnn.2017.12380
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effect of Curcumin/BMP-2 Loaded in HA/PLL Hydrogels on Osteogenesis In Vitro and In Vivo

Abstract: In the present study, we evaluated the potential of poly-l-lysine/hyaluronic acid (HA/PLL) hydrogels containing curcumin (CUR) and bone morphogenetic protein-2 (BMP-2) as bone tissue regeneration scaffolds. Hydrogels HP-1˜2 were formed by amide bonds via the condensation reactions between 0.02 μmol HA and 0.06–0.12 μmol poly-l-lysine · hydrobromide (PLL · HBr). Physical, chemical, and thermal analyses revealed that the amount of PLL · HBr significantly influenced hydrogel properties. Based on an In Vitro MG-63… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Human osteosarcoma derived cells exhibited good viability, proliferation, ALP activity and calcium deposition. In comparison with other polymers, the high bone formation induced by low burst followed by sustained release, guaranteed good results in in vivo tests, too [105,106]. In another study, the hyaluronic acid has been combined with chondroitin 6 sulphate and dermatan sulphate.…”
Section: Natural Polymersmentioning
confidence: 96%
“…Human osteosarcoma derived cells exhibited good viability, proliferation, ALP activity and calcium deposition. In comparison with other polymers, the high bone formation induced by low burst followed by sustained release, guaranteed good results in in vivo tests, too [105,106]. In another study, the hyaluronic acid has been combined with chondroitin 6 sulphate and dermatan sulphate.…”
Section: Natural Polymersmentioning
confidence: 96%
“…BMP-2 is one the most widely studied BMPs with the most potent bone inductive activity and has been reported to induce osteogenic differentiation in vitro ( 39 , 40 ) and bone formation in vivo ( 41 ). The BMP-2 signaling pathway is a vital positive modulator of bone homeostasis ( 42 , 43 ). BMP-2 binding to its receptors regulates target genes, such as Runx2 and Osterix ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the bioavailability of curcumin is limited due to low aqueous solubility, extremely rapid systemic elimination, and inadequate tissue absorption and degradation (Anand et al, 2007). The high concentration of curcumin caused by inappropriate release behavior is not conducive to cell adhesion and proliferation (Scharstuhl et al, 2009;Jain et al, 2016;Kim et al, 2017). Therefore, the bioavailability and sustained-release kinetics of curcumin have been improved through biomaterial-based administration methods used for the inhibition of osteoclasts and osteosarcoma (Dhule et al, 2012;Heo et al, 2014;Chen X. et al, 2015;Kheiri Manjili et al, 2017;Verma et al, 2019) (Figure 2).…”
Section: Alkaloid Curcuminmentioning
confidence: 99%
“…A study demonstrated that various amounts of curcumin/ BMP-2-loaded poly-L-lysine/hyaluronic acid hydrogels resulted in increased MG-63 cell proliferation after 3 days of culture, and by controlling the amounts of curcumin and BMP-2, the hydrogels showed better osteogenesis with higher in vitro ALP activity and calcium deposition and better in vivo new bone regeneration, as shown by micro-CT analyses. Notably, the incorporation of greater than 15 μM curcumin had negative effects on the proliferation of human osteosarcoma MG-63 cells (Kim et al, 2017). Successful treatment of osteosarcoma requires postsurgical bone defect repair as well as the complete eradication of bone tumor cells in the surrounding tissues (Ma et al, 2018).…”
Section: Alkaloid Curcuminmentioning
confidence: 99%